2020
DOI: 10.1002/er.5900
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement study of an integrated photovoltaic system for offshore power production

Abstract: Sustainable energy is one of the main options for resolving energy problems and climate change issues. Solar energy is one of the main promising renewable energy sources, which can be captured and converted to electrical energy through photovoltaic (PV) panels. In the open literature, it is shown that having two PV panels integrated into a back-to-back configuration placed on naturally reflective surfaces provides the potential of doubling the total power produced by a single-faced PV panel with the appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The evaluation of the PV systems was carried out by modelling and simulating the photovoltaic modules in the simulation software COMSOL Multiphysics. It was found that the total energy generation of the east-facing photovoltaic modules was 38.0% better than the conventional system [20]. Various environmental factors such as dust accumulation, shading and bird droppings affect the performance of photovoltaic system [21].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the PV systems was carried out by modelling and simulating the photovoltaic modules in the simulation software COMSOL Multiphysics. It was found that the total energy generation of the east-facing photovoltaic modules was 38.0% better than the conventional system [20]. Various environmental factors such as dust accumulation, shading and bird droppings affect the performance of photovoltaic system [21].…”
Section: Introductionmentioning
confidence: 99%
“…F I G U R E 1 Global LCOE values of renewables (data from 15 ) Offshore solar systems are analyzed with thermodynamic-based approaches from energy and exergy points of view. Al-Zareer et al 17 studied the performance improvement of an integrated photovoltaic system for offshore applications. Their proposed system produced 38% more power during January, in Ottawa, Canada, than the single face conventional PV system.…”
Section: Introductionmentioning
confidence: 99%
“…As investigations show that, 60 to 80% of bioethanol operating cost is accounted for separation and purification processes. 1 In this study, as it is mentioned before the bioethanol production process, separation/purification of the final product is analyzed since it is the most difficult processes; as the novel point of the study, the reached aim is to reduce the production drawbacks of the process, energy consumption reduction and operating cost resulting from it. In comparison with the previous studies, effective parameters are applied in the analysis along with to get more comprehensive view of the bioethanol production.…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers about bioethanol production show that this process should be studied in detail considering cost and energy consumption to make it practically cost‐effective. As investigations show that, 60 to 80% of bioethanol operating cost is accounted for separation and purification processes 1 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation